#TITLE_ALTERNATIVE# - PUSAP (NIM: 10107009); Pembimbing : Wono Setya Budhi, Ph. D., SUHENDI
Norm equivalence between convolution operator in the discrete space (discrete analogue) and convolution in the continue space was given by Magyar, Stein, and Wainger in [3] focusing on Fourier transform. Hilbert transform was written sophisticately by King in [1]. This undergraduate thesis shows the relation between [3] and [1] regarding Hilbert transform as a convolution. The …rst part gives some details for [3], the second part narrows down the way of …nding the Hilbert transform using the complex function approach, especially via Poisson Integral Formula, and the last part investigates norm boundedness on the analog of the discrete Hilbert transform. Although there is nothing new, this undergraduate thesis gives the more simple perspective on those matters for the easing of reading a book or paper for undergraduate students.